2004
DOI: 10.1158/0008-5472.can-04-0795
|View full text |Cite
|
Sign up to set email alerts
|

P-Cadherin Is Up-Regulated by the Antiestrogen ICI 182,780 and Promotes Invasion of Human Breast Cancer Cells

Abstract: P-cadherin expression in breast carcinomas has been associated with tumors of high histologic grade and lacking estrogen receptor-␣, suggesting a link between these proteins. In the MCF-7/AZ breast cancer cell line, blocking estrogen receptor-␣ signaling with the antiestrogen ICI 182,780 induced an increase of P-cadherin, which coincided with induction of in vitro invasion. Retroviral transduction of MCF-7/AZ cells, as well as HEK 293T cells, showed the proinvasive activity of P-cadherin, which requires the ju… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 49 publications
4
83
1
2
Order By: Relevance
“…Previous studies have shown that P-cadherin expression in breast carcinomas is able to identify a subgroup of lesions with a more aggressive behaviour and poor patient survival (Peralta Soler et al, 1999;Gamallo et al, 2001;Paredes et al, 2002Paredes et al, , 2004Paredes et al, , 2005Paredes et al, , 2008. Similar associations between P-cadherin expression and poor prognosis are described in other cancer models, namely endometrial, cervical, gastric and pancreatic carcinomas (Stefansson et al, 2004;Longatto Filho et al, 2005;Taniuchi et al, 2005).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Previous studies have shown that P-cadherin expression in breast carcinomas is able to identify a subgroup of lesions with a more aggressive behaviour and poor patient survival (Peralta Soler et al, 1999;Gamallo et al, 2001;Paredes et al, 2002Paredes et al, , 2004Paredes et al, , 2005Paredes et al, , 2008. Similar associations between P-cadherin expression and poor prognosis are described in other cancer models, namely endometrial, cervical, gastric and pancreatic carcinomas (Stefansson et al, 2004;Longatto Filho et al, 2005;Taniuchi et al, 2005).…”
Section: Discussionmentioning
confidence: 67%
“…Our group has previously shown in vitro that, using HEK 293 T cells as a model system, P-cadherin has a pro-invasive activity, through its juxtamembrane domain (Paredes et al, 2004). In contrast, in highly invasive melanoma cell lines, P-cadherin overexpression is able to promote the formation of cell-cell contacts and counteract invasion (Van Marck et al, 2005), showing that it may function either as an invasion promoter or as an invasion suppressor depending on tissue specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…194), and cell adhesion molecules (e.g., E-cadherin and P-cadherin; refs. [195][196][197][198] have been studied as possible breast tumor markers. In this context, osteopontin also represents an interesting alternative as a breast cancer marker.…”
Section: Breast Cancer Biomarkersmentioning
confidence: 99%
“…Hormonal regulation of cadherins levels has been shown for the estrogen receptor, which modulates Snail repression of E-cadherin levels during invasive growth of breast cancers (reviewed in Fearon, 2003). In addition, antiestrogens result in upregulation of P-cadherin occurs in proliferative, invasive breast cancer cells (Paredes et al, 2004).…”
Section: Ecr Is Required For Fc Migration and Differentiationmentioning
confidence: 99%